N,N-bis(2,3-Dihydroxypropyl) Octadecylamine for Liquid–Liquid Extraction of Boric Acid - Biçak, Niyazi; Gazi, Mustafa; Bulutcu, Nusret (Informa UK Limited, 2003)
N,N-bis(2,3-dihydroxypropyl) octadecylamine (BPO) has been synthesized by condensation of octadecylamine with 2 M of 1-chloro 2,3-propandiol (1-chloroglycerol) in alcohol, in high yields (88.0%). Its solution in 2-ethyl hexanol has been demonstrated to be very efficient in liquid–liquid extraction of boric acid from aqueous solutions. Two vicinal-diol functions of BPO make it versatile reagent for boron extraction. The long aliphatic chain involved provides solubility in organic solvents. At relatively low boric acid concentrations, i.e., 1.2% (w/w), about 98% of BPO involves boron chelation, in nonbuffered conditions. The role of the tertiary amine function is entrapping acidic proton resulting from possible anionic borate complexation. In the study, pH dependence of the boric acid extraction and regeneration conditions of the chelating agent has been investigated. Overall results indicate that the boron complex is stable above pH 4.7 and the presence of some common foreign ions such as Ca(II) and Mg(II)...